The systemic response to surgery triggers the outgrowth of distant immune-controlled tumors in mouse models of dormancy - Krall, Jordan A; Reinhardt, Ferenc; Mercury, Oblaise A; Pattabiraman, Diwakar R; Brooks, Mary W; Dougan, Michael; Lambert, Arthur W; Bierie, Brian; Ploegh, Hidde L; Dougan, Stephanie K; Weinberg, Robert A (Science translational medicine, 2018)
Patients undergoing surgical resection of primary breast tumors confront a risk for metastatic recurrence that peaks sharply 12 to 18 months after surgery. The cause of early metastatic relapse in breast cancer has long been debated, with many ascribing these relapses to the natural progression of the disease. Others have proposed that some aspect of surgical tumor resection triggers the outgrowth of otherwise-dormant metastases, leading to the synchronous pattern of relapse. Clinical data cannot distinguish between these hypotheses, and previous experimental approaches have not provided clear answers. Such uncertainty hinders the development and application of therapeutic approaches that could potentially reduce early metastatic relapse. We describe an experimental model system that definitively links surgery and the subsequent wound-healing response to the outgrowth of tumor cells at distant anatomical sites. Specifically, we find that the systemic inflammatory response induced after surgery promotes the emergence of tumors whose growth was otherwise restricted by a tumor-specific T cell response. Furthermore, we demonstrate that perioperative anti-inflammatory treatment markedly reduces tumor outgrowth in this model, suggesting that similar approaches might substantially reduce early metastatic recurrence in breast cancer patients.